Impact of zero valent iron aging on reductive removal of technetium-99. Issue 3 (June 2020) - Emerson, Hilary P.; Gebru, Abraham; Boglaienko, Daria; Katsenovich, Yelena P.; Kandel, Shambhu; Levitskaia, Tatiana G.
Highlights: Impact of aging on zero-valent iron reduction capacity. Technetium reductive removal from solution by zero-valent iron. Decreased technetium reduction by zero-valent iron after two weeks. Abstract: Zero valent iron (ZVI) is a promising material for reductive removal of technetium-99 from industrial waste streams. One potential application is treatment of radioactive waste streams generated during processing of legacy low activity aqueous waste that is currently stored in tanks at the Hanford Site. However, there is a lack of understanding of the useful lifetime of ZVI for treatment and the changes in reductive removal of Tc over time under aerobic conditions. In this research, we studied the reductive removal of Tc(VII) by ZVI aged in 0.08 M NaCl solutions from 0 to–30 days. Our results show that ZVI could be used to remove Tc(VII) from aqueous solutions by reduction to the less soluble and relatively immobile Tc(IV) with greater than 99 % removal efficiency in three hours. Moreover, greater than 90 % of Tc remained in the solid phase for up to one week. However, after 10 days of ZVI aging, a significant decrease in removal of Tc occurs (55 % maximum removal) followed by negligible removal after aging for two weeks or more which is consistent with diminished reductive capacity due to formation of iron oxides on the surface. The uptake results correlate with XRD and FTIR analysis showing an increase in magnetite followed by maghemite and goethite with aging time.